Development of School Culture for School Quality Improvement - eviana hikamudin (Jurnal Administrasi Pendidikan, 2022)
The aims of this article are to elaborate on the importance of building a school culture to improve the quality of schools through the implementation of school-based management. The study used a literature study approach by the content analysis method. The conclusion of this study is there is a positive impact of the school culture in order to improve the quality of schools by school-based management implementation. This article provides the informa-tion about student’s competences base on report of PISA and National Assessment in literacy, numeracy, character surveys, and learning environment surveys. Gives the information about teacher’s competences base on the results of teacher competency measurements and an outlining the factors that cause the low quality of the school. The cause the quality of the school is low of students and teacher’s competences is minimum effort of the school in improving a school culture to achieve the school quality through the implementation of school-based management. The conclusion of this study is there is a positive impact of the school culture in order to improve the quality of schools by school-based management implementation.